Pelatihan Pembuatan Pupuk Organik di Gereja Protestan Persekutuan Desa Parhorboan - Erman Saragih; Bestian Simangunsong; Junjungan Simorangkir; Nurelni Limbong; Warseto Freddy Sihombing; Tifany Tamba; Nicolas Sinaga; Despriana Rismawati Tumangger; Veronika Uliarta Sinaga; Sarnita -; Listrawati Bancin Bancin; Delima Padang; Tesdiami Berutu; Indra Putra Adi Sinamo; Adi Sinamo; Helen Angelita Purba; Firman Gani Manik; Dicky Cibro (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
The portrait of natural damage in Parhorboan Village, North Tapanuli Regency is a concern and concern for the Theology Study Program to carry out Community Service activities. In addition to the rampant logging of protected forests, chemical fertilizers also damage the humus content of the soil and indirectly create disaster for humans and God's creation. Congregation of the Protestant Communion Church as spiritual beings must be involved in caring for the land and nature for sustainable innovation. Participants in this Community Service activity were lecturers and fifth semester students of the Theology study program at the Tarutung Christian Institute and the Parhorboan Congregation. The purpose of this Community Service activity is not limited to enriching the Ecotheology Course but also providing aspects of knowledge and skills for the congregation in making organic fertilizer. The high price of chemical fertilizers helps farmers in accessing agricultural fertilizer needs. Therefore, the manufacture of organic fertilizers is one solution. By using organic fertilizers, the soil content is not damaged, the topsoil is maintained, and beautiful nature becomes real.